ANALYSIS OF CONTRACTS BETWEEN 3PL PROVIDERS AND MANUFACTURERS OR RETAILERS FOR ATTAINING HIGHER SERVICE LEVEL COLLABORATIVELY AND FOR DECREASING THE SUPPLY CHAIN COSTS - RAJANA, K.N. (2016)
The analysis of the past records of the 3PL service providers reveal that they have a bright future since majority of the companies world-wide are intending to outsource their logistics services. This particular study has been focused on the integration of 3PL services into supply chain in UK. Generally, the firms in UK such as Shell, P&G, Samsung and Debenhams prefer outsourcing their various logistics services including packaging, logistics information systems, labelling, distribution and consolidation, warehousing and transportation. This particular study intended to determine how the collaboration may cut down costs and decrease the average delivery lead time as well as improves the logistical service and operational performance and how it can optimize the supply chain management. The research also aimed to analyse the methods that can be utilized to incentivize the parties involved in collaborating. Lastly, the research includes various case studies to determine how companies carry out such collaborations in practice, for example, DHL-Debenhams and other successful partnerships of logistics companies like Amazon-Yodel, Volvo Cars-DHL, and P&G Amazon have optimised the supply chain performance. In order to accomplish the predetermined goals, the researcher adopted secondary qualitative research methodology based on inductive approach. The researcher analyzed various case studies and performed an extensive review of past studies. The findings of the study revealed that several aspects including trust, commitment, shared risk and rewards and communication influence the sustainable corporation between 3PL service providers and Supply chain partners. Moreover, the findings revealed several large firms such as P&G, Samsung utilize services from third party logistics to optimize their supply chain performance. The advantages attained by firms including Debenhams, Volvo Cars and P&G by outsourcing their major logistics processes and operation to the reliable 3PL such as DHL, Yodel include cost reduction, cut down asset investment and enhanced customer service. Moreover, it was observed that longer contractual length indicates that the 3PL dedicates more time, resource and effort to the project. This can also be advantageous to 3PL providers as they can commit to more cost effective leases and investments can be slowly poured into the project at regular intervals.